THE EFFECT OF USING ICE BREAKING ON LEARNING MOTIVATION EARLY CHILHOOD IN RA AL-MAHABBAH BATANG KUIS - Kharida Shaleha (Jurnal Scientia, 2023)
Based on the results of observations made by researchers on children, children's learning motivation varies. There are children who have a good level of learning motivation, but there are also children who have a poor level of learning motivation. The purpose of this study was to determine the effect of ice breaking on early childhood learning motivation at RA Al Mahabbah Batang Kuis. This study used a Pre-Experimental Design, namely with one of the Pretest-Posttest groups (One Group Pretest-Posttest Design) as the research design. Data collection techniques from this study are observation, interviews and documentation. The subjects of this study were early childhood at RA Al Mahabbah Batang Kuis with a total of 21 children. The observation results H0 are rejected and H1 is accepted, so it can be concluded that ice breaking has an effect on early childhood learning motivation at RA Al Mahabbah Batang Kuis.